Pre-service teachers' progressive reflective practices using weekly journals in an action research project - Lee, Seung Chun (Asia TEFL, 2018)
Developing teachers who can critically reflect on their teaching practice is one of the goals of many teacher education programs (David, 2005). However, current teacher training programmes do not allow pre-service teachers sufficient time for reflection and do not exploit fully the opportunities offered. As a result, they focus mainly on surface level reflection such as knowledge of the subject matter, pedagogic skills, and classroom management, to the neglect of pedagogical and critical levels of reflection such as the connections between theoretical principles and practice, and the ethical implications and consequences of their instructions on students (Larrivee, 2008). One of the best ways to encourage teachers’ reflection is through the keeping of a teaching journal (Thornbury, 2006). When teachers reflect on their teaching practices, they can understand them better, and take steps to improve them. However, the majority of journal studies are carried out with in-service teachers and with pre-service teachers over the teaching practicum (Lee, 2007). There is no reason why learning to reflect should wait until the practicum for pre-service teachers. Teacher educators need to help pre-service teachers develop reflective thinking as soon as their learning process starts, so that they can experience success in the classroom both as teacher candidates and later as teachers. Thus, the current study focuses on the development of reflective practices in a supervisory project carried out by the preservice teachers of English at a national university in Malaysia. This report aims at providing an account of how pre-service teachers progressed along a continuum of three levels of reflective practice (surface reflection, pedagogical reflection, and critical reflection) to be critically reflective through the experience of keeping reflective journals in an action research project.